The effects of cyanide on hard corals :implication on cyanide fishing on coral reefs in north borneo - Atack, Katherine (Universiti Malaysia Sarawak, (UNIMAS), 2003)
There are many threats such as over-exploitation pollution, urban and industrial development and destructive finishing practices, which are damaging and destroying a large majority of the world's reefs. Cyanide fishing is used extensively throughout Southeast Asia for both the aquarium trade and increasingly for the live reef fish food trade (LRFFT). The use of cyanide has been proven to be harmful to smaller fish, other reef fauna, and it causes corals to bleach and die at concentrations much lower than used by the fishermen. This study was conducted off the island of Pulau banggi on the northeastern coast of Sabah, East Malaysia. Eight coral species were used; Acropora nobilis, Goniopora djiboutensis, Pachyseris speciosa, Pavona clavus, Stylophora pistillata, Galaxea astreata, Hydnophora rigida and Euphyllia glabrrescens.